2022
DOI: 10.1186/s12875-022-01630-0
|View full text |Cite
|
Sign up to set email alerts
|

Can the implementation of family doctor contracted service enable the elderly to utilize primary health care services more equally? empirical evidence from Shandong, China

Abstract: Background While the elderly are facing greater health risks, they also face more serious inequalities in utilization of medical services. The family doctor contracted service is the core policy of the Chinese government to cope with aging and to achieve the outcome that everyone has the right to primary health care. However, previous research has neither revealed the degree of inequality in the use of contracted services among the elderly in China, nor has it revealed what factors are related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Another possible reason was that the older adult and patients with chronic diseases were key service objects of FDCS, and they can receive priority service, door-to-door service, and long-term prescription service (45), which encourages them to maintain the doctor-patient relationship formalized by an FDCS contract. One study suggested that primary medical resources would benefit more residents who needed timely medical treatment, and the allocation of medical resources would also be more reasonable (46). Thus, our results suggest that persisting with improving priority services for key population groups (the older age group and the group with chronic diseases) may help achieve a better renewal rate for the Chinese FDCS and a more rational allocation of health resources.…”
Section: Discussionmentioning
confidence: 74%
“…Another possible reason was that the older adult and patients with chronic diseases were key service objects of FDCS, and they can receive priority service, door-to-door service, and long-term prescription service (45), which encourages them to maintain the doctor-patient relationship formalized by an FDCS contract. One study suggested that primary medical resources would benefit more residents who needed timely medical treatment, and the allocation of medical resources would also be more reasonable (46). Thus, our results suggest that persisting with improving priority services for key population groups (the older age group and the group with chronic diseases) may help achieve a better renewal rate for the Chinese FDCS and a more rational allocation of health resources.…”
Section: Discussionmentioning
confidence: 74%
“…This study found a significant association between FDCS and subjective well-being. This can be explained by the fact that the government provides family doctors with comprehensive training to improve their skills, competence, and confidence, resulting in reduced dissatisfaction with local medical services among middle-aged and older people and alleviated healthcare inequality 43 , which in turn improves resident’ subjective well-being. Family doctors could provide better services to the population and maintain independence 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Among this group, approximately 65% are dealing with chronic diseases, making elderly individuals with chronic conditions a significant concern in both healthcare and society. 2 The existing medical resources and care service models have proven inadequate to meet the escalating demand. 3 , 4 In this context, the Chinese government has issued notifications in both 2019 and 2020 to drive forward the implementation of pilot projects for “Internet Plus Nursing Services”.…”
Section: Introductionmentioning
confidence: 99%